2021
DOI: 10.24198/jkp.v9i1.1645
|View full text |Cite
|
Sign up to set email alerts
|

The Structure, Process, and Outcome of Mentorship on Survivor with Schizophrenia: A Case Study

Abstract: The personal recovery paradigm in schizophrenia patients require a change of service. One of the changes that can be made to support the schizophrenia recovery process is a change in the concept of the relationship between patients and nurses. Nurse mentorship for schizophrenia patients is a new terminology of innovation in a supportive relationship between health workers and patients. At present, it is not known how the structure, process, and outcome of mentorship to schizophrenia survivors. This study aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
1
4
0
1
Order By: Relevance
“…Similar findings have been echoed in other Asian studies, which showed that people were likely to hide their symptoms or not talk about them for fear of being viewed as different or weird (Gopal et al, 2020; M. M. Lam et al, 2011; Suryani et al, 2022; Wang, 2012). Hence, by not being able to live authentically, participants struggled to find a reason to carry on, with many expressing the desire to become numb or to give up entirely as they could not see the end to their challenges.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similar findings have been echoed in other Asian studies, which showed that people were likely to hide their symptoms or not talk about them for fear of being viewed as different or weird (Gopal et al, 2020; M. M. Lam et al, 2011; Suryani et al, 2022; Wang, 2012). Hence, by not being able to live authentically, participants struggled to find a reason to carry on, with many expressing the desire to become numb or to give up entirely as they could not see the end to their challenges.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, there has been a growing body of research in Asian cultural environments which demonstrates the importance of these efforts as they bring new contextual factors that need to be considered (Gearing et al, 2022; Lai et al, 2021; J. S. H. Lam et al, 2021; Meheli et al, 2021; Subandi et al, 2021; Suryani et al, 2022; Tasijawa et al, 2021; Tsoi et al, 2022; Yoder et al, 2021). Hence, this study sought to deepen these ideas by exploring and shedding light on the lived experiences of people who experience mental ill health in Singapore.…”
mentioning
confidence: 99%
“…This encouraging finding suggests that, upon exposure to perspectives on the personal-recovery approach, they might better appreciate its clinical value for MHCs. However, within the context of Asia, cultural differences are inherent to the construct of personal recovery and its associated features (Bingham and Kelley, 2022;Fujisawa, 2023;Lai et al, 2021;Lam et al, 2021;Lee et al, 2021;Meheli et al, 2021;Suryani et al, 2022;Tasijawa et al, 2021;Tsoi et al, 2022;Yu et al, 2021aYu et al, , 2021b, for which further research is thus warranted to validate these findings and explore potential differences. For example, in Singapore, recovery is more intertwined with community acceptance and social cohesion than western perspectives which tend to be viewed as a more individual experience (Kuek et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This support arises from the social environment and family environment. Interventions also involve family and social skills to increase hope and a better quality of life (Kurniawan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%